ChemInform Abstract: A Practical One‐Pot Procedure for the Synthesis of N—H Isoquinolones. Issue 29 (1st July 2013) - Lu, Shaonan; Lin, Yingfu; Zhong, Hongban; Zhao, Kang; Huang, Jianhui
Abstract An efficient approach to the title skeleton is achieved through Pd‐catalyzed reaction of N‐alkoxybenzamides with alkynes followed by NaH‐mediated N—O bond cleavage.